PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 89 PEKANBARU - Sri Rahayu; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted because of the result learning social study class V SDN 89 Pekanbaru. Based on the data obtained from the at SDN 89 Pekanbaru replay test results were completed only 16 people (35%) and who did not complete as many as 24 people (65%) of the 40 students with the acquisition value of the average grade is 70. THIS RESEARCH IS A CLASSROOM ACTION RESEARCH (PTK) which amis to improve learning outcomes IPS V grade students of SDN 89 Pekanbaru apply model contextual teaching and learning (CTL). Application of learning models Contextual Teaching and Learning (CTL) in class V SDN 89 Pekanbaru improved quality learning seen from the activities of teachers who have increased, in the first cycle the average percentage of teacher activity is 78.57% with good category (B) increased to 96 , 42% in the second cycle with excellent category (A). Student activity also increased, in the first cycle the average percentage of student activity is 75% good category (B) increased to 96.42% with very good category (A) in the second cycle. Application of learning models Contextual Teaching and Learning CTL) can improve learning outcomes in social studies class V students of SDN 89 Pekanbaru IPS graders. Obtaining the average value of the base before being held test score is 64.62. Then increased after the implementation of the model Contextual Teaching and Learning (CTL) at UH I, the value of the average student becomes 68.87. UH increased again in the second with an average score of students into 77.75. Improving student learning outcomes from basic score to UH I amounting to 15%, while improving student learning outcomes from basic score to UH II is 35%.Keywords: Contextual Teaching and Learning, learning outcomes IPS